Assessment of compliance to anti-rabies vaccine post-exposure prophylaxis in a tertiary care centre in Jammu - Chalotra, Ritika; Zaffer, Imran; Khajuria, Nancy (International Journal Of Community Medicine And Public Health, 2025)
Background: Rabies remains a fatal global health threat, with India bearing a significant burden. Anti-rabies vaccine’s (ARV) post-exposure prophylaxis is crucial, yet poor adherence hinders eradication efforts and for improving outcomes of post-exposure prophylaxis we need to know about reasons behind non-compliance and delayed compliance. This study investigated ARV PEP adherence and its contributing factors at GMC, Jammu. Methods: This Study was conducted among 594 animal bite victims (Category 2 and 3) at GMC Jammu's Anti-Rabies Clinic and study subjects were selected via convenience sampling method from September 2022 to July 2023. Data on demographics, bite characteristics, and wound care were collected, and ARV adherence was monitored. Reasons for non-compliance or delayed compliance were ascertained via telephone. Results: Of participants, 74.2% completed the ARV course. However, about 22.1% had delayed adherence, while 3.7% had non-compliant. Delayed compliance’s most common reasons were residence far away from clinic, work location outside Jammu, forgotten dates, negligence and loss of wages. Non-compliance was primarily due to negligence and health issues. There was no statistically significant association found between full compliance and combined (delayed and non-compliance) with factors such as age, residence, education, gender, category of bite, number of wounds, type of animal bite, wound washing practices, method of wound washing, or duration of wound washing (p>0.05). Chi-square test was applied for testing significance. Conclusions: The study highlights considerable delayed and non-compliance with ARV, largely driven by patient negligence and health problems. This necessitates enhanced awareness, comprehensive patient education, and practical solutions to improve ARV PEP adherence and reduce rabies mortality in India.